TRANSFORMATION OF LUDRUK PERFORMANCES: FROM POLITICAL INVOLVEMENT AND STATE HEGEMONY TO CREATIVE SURVIVAL STRATEGY - Ikwan Setiawan; Sutarto . (Faculty of Cultural Sciences, Universitas Gadjah Mada, 2014)
This article discusses the transformation of ludruk performances, from Soekarno to Reformation era. In discussing the problem, we apply a cultural studies perspective. From our analysis, there are three findings related to the discursive transformation of ludruk stories. Firstly, in the era of Soekarno, many ludruk groups joined Lembaga Kebudayaan Rakyat (Lekra/Institute of People’s Culture), which had many ideological similarities with Partai Komunis Indonesia (PKI/ Indonesian Communist Party). Consequently, ludruk groups performed some provocative stories that exposed the problems of lower-class people and criticized Islamic religious beliefs. Secondly, after the bloody 1965 tragedy, the regional military apparatuses controlled ludruk groups and their performances, including the stories. In this era, ludruk stories supported the New Order regime’s national development programs and raised people’s consensus on the significance of militarism through popular stories about people’s resistance to colonizers. Thirdly, in the Reformation era, some ludruk groups make newer, interesting stories about many complicated social problems in contemporary society. Finally, we conclude that this mode of transformation through creating newer, social problem-based stories that intertwine with historical conditions has deep historical roots in ludruk performances. In addition, during the Reformation period in whichmarket capitalism becomes a dominant ideology and practice, such newer stories and breakthroughs of staging may become a suitable creative survival strategy for ludruk groups in the midst of techno-cultural popularity as the dominant taste and orientation in societies.